A pet for pete eaudiobook - Dean, James (My First I Can Read: Pete the Cat., 2014)
Pete the Cat can't wait to get a new pet! He gets a goldfish he names Goldie. Pete paints a cool painting of Goldie and now everyone wants a piece of it! But Pete doesn't have enough time to make one for everyone. Will Pete find a way to have fun painting Goldie and have time to finish his homework? From New York Times bestselling artist and author James Dean, Pete the Cat: A Pet for Pete is a My First I Can Read Book, which means it's perfect for shared reading with a child.